The Educator’s Guide to AI: What You Can’t Afford Not to Know - Abdulmumin, Abdulmumin Ibrahim (Al-Wazan: Journal of Arabic Education, 2025)
This modest study, titled "What Every Teacher Must Know About Using Artificial Intelligence in Education", addresses the growing need for educators to understand and effectively integrate Artificial Intelligence (AI) into the teaching and learning process. The research problem lies in the insufficient awareness and knowledge among many teachers regarding how to employ AI tools in preparing educational content and integrating them into classroom practices. As a result, the benefits of modern technologies in enhancing teaching strategies remain underutilized. The primary objectives of this research are to: identify fundamental AI concepts relevant to education; explore practical applications of AI in content development; analyze the opportunities and challenges educators face when implementing AI; and offer actionable strategies for using AI tools in classroom settings. Using a descriptive-analytical method, the study examines AI as a branch of computer science capable of problem-solving and decision-making. It finds that AI can significantly support various educational functions, including school administration, language skills instruction, curriculum design and planning, creation of educational videos, generation of assessments, and the development of engaging presentations. Furthermore, AI tools can promote variety and innovation in classroom activities, contributing to more personalized and effective learning experiences. The study recommends training programs to equip teachers with AI competencies, gradual integration of AI tools into curricula, and technical support systems to ensure sustainable implementation. This research contributes to the ongoing discourse on educational innovation by empowering teachers to adapt to technological advancements and enrich the quality of education